A nationwide multicenter study of the Cochlin tomo-protein detection test: clinical characteristics of perilymphatic fistula cases. (10th March 2017) - Matsuda, Han; Sakamoto, Kei; Matsumura, Tomohiro; Saito, Shiho; Shindo, Susumu; Fukushima, Kunihiro; Nishio, Shin-ya; Kitoh, Ryosuke; Shibasaki, Osamu; Ito, Akinori; Araki, Ryuichiro; Usami, Shin-ichi; et al.
Abstract: Objective: To investigate the positive rate for the Cochlin tomo-protein (CTP: an inner ear-specific protein) detection test among patients with inner ear-related clinical manifestations and evaluate the clinical characteristics of definite perilymphatic fistula (PLF). Methods: We have performed an ELISA-based CTP detection test using middle ear lavage (MEL) samples from 497 cases of suspected PLF enrolled from 70 clinical centers nationwide between 2014 and 2015. In addition to the CTP-positive rate, audio-vestibular symptoms were compared between CTP-positive and -negative cases. Results: 8–50% of patients in category 1 (trauma, middle and inner ear disease cases), and about 20% of those in categories 2, 3 and 4 (external origin antecedent events, internal origin antecedent events, and without antecedent event, respectively) were positive for CTP. In category 1 cases, the earlier tested samples showed a higher CTP-positive rate, whereas no differences were observed in categories 2, 3 or 4. The characteristic clinical features in the earlier tested cases were nystagmus and fistula sign in CTP test-positive cases in category 1, and streaming water-like tinnitus in those in categories 2, 3 and 4. Conclusion: The present study clarified that CTP detection test-positive patients exist at considerable rates among patients with inner ear-related manifestations.